ACTUALIZATION OF THE ZONE OF PROXIMAL DEVELOPMENT OF JUNIOR SCHOOLCHILDREN WITH MENTAL RETARDATION BY MEANS OF A LITERARY GAME - M.E. Starostina; D.A. Starostin (Krymskij Naučnyj Vestnik, 2017)
The article discusses the concept of "zone of proximal development" from the standpoint of the cultural-historical approach, raises the problem of specificity of this concept in the modern system of education, justifies the use of literary games as an effective means of mental development of younger students with disabilities.